PENGEMBANGAN MEDIA INTERAKTIF BERBASIS SITUS CANDI DI JAWA TENGAH UNTUK MENINGKATKAN HASIL BELAJAR DAN KESADARAN KEBERAGAMAN BUDAYA SISWA MAN 1 KOTA MAGELANG - Fauziah, Annisaak Sholikhatun; Wasino, W.; Musadad, Akhmad Arif (Sebelas Maret University (UNS), 2014)
This research is a need analysis in nature by developing finding, yielding, and improving a History learning media as well as testing the effectiveness of the product so that it becomes more effective, efficient, meaningful, and up to date. The product expected is a History learning module based on the temple sites in Central Java, namely: Ngawen temple, Mendut temple, Selogriyo temple, and Candi Asu Sengi temple, which is packed in an Interactive Media to improve the students’ learning result and historical variety awareness.This research used the Research and Development (R&D) method. Its procedure included (1) preliminary research, (2) learning media development, (3) learning media implementation, and (4) learning media (developed product) testing. The subjects of research were the students in Grade X of State Islamic Senior Secondary School of Magelang City, and the objects of research were the students’ learning result and cultural diversity awareness. The development of the interactive learning media based on the temple sites in Central Java is tested with validity testing by learning material expert and learning media expert, one by one testing, and field testing. Each has the average score of greater than 4, meaning that the developed learning media is good and feasible to be used as a research instrument. The result of the effectiveness testing shows that the learning result of the students instructed with the interactive learning media based on the temple sites in Central Java is better than that of the students instructed with the students’ Worksheet as indicated by the result of the Wilcoxon test where both the experimental group and the control group have the p-value = 0.000 (p < 0.05). Thus, there is a significant difference between the experimental group’s score difference (17.5 ± 9.806) and control group’s score difference (7.67 ± 8.412); the former is greater than the latter.